Exploring Reduced-Fat Banana Flavored Milk for Sustainable Food Security: Physicochemical, Microbiological and Sensory Insights (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
This study explores the physicochemical, microbiological, and sensory properties of an innovative reduced-fat banana milk cube (RFBMC), designed to address food security by providing a nutritious, shelf-stable snack. The formulation, utilizing Pisang Berangan (Musa paradisiaca) puree and milk powder, aims to retain essential nutrients and improve long-term usability, ensuring more sustainable access to nutritious food. Four formulations, which are RFBMC 0 (0% BP), RFBMC 1 (20% BP), RFBMC 2 (30% BP), and RFBMC 3 (40% BP), were developed and analyzed to determine their properties. Physicochemical analyses, including hardness, pH, water solubility index, and proximate composition, revealed significant differences among the formulations, with RFBMC 1 exhibiting the most desirable characteristics. Sensory evaluations conducted with 50 panelists identified RFBMC 1 as the preferred formulation due to its balanced aroma, flavor, texture, and hardness, achieving the highest overall acceptance score. Microbiological analysis confirmed the safety of RFBMC 1 and RFBMC 0, with no detection of harmful pathogens such as Escherichia coli, Salmonella spp., coliforms, or Staphylococcus. Although RFBMC 1 recorded a higher total plate count (532,000 CFU/g) compared to RFBMC 0 (1,000 CFU/g), it remained within acceptable limits. The low-fat content of RFBMC 1 (0.77%), its optimal carbohydrate content (36.40%), and high antioxidant levels (51.26%) contributed to its nutritional appeal and consumer preference. The findings reveal that reduced-fat banana milk cubes (RFBMC) serve as a healthier, sustainable alternative to traditional dairy snacks, meeting the growing consumer demand for functional foods and supporting food security by providing an accessible, nutrient-packed, and shelf-stable option.
Keywords: Musa paradisiaca; Reduced-Fat Banana Milk Cube; Physicochemical Properties; Microbiological Analysis; Sensory Properties